HUBUNGAN KESEHATAN KELUARGA DENGAN KONDISI BIO-PSIKO-SOSIO-SPIRITUAL PASIEN COVID-19 - Nasrudin Nasrudin; Umi Azizah Kusumaningrum; Siti Urifah (Jurnal EDUNursing, 2021)
Abstract                Coronavirus Diseases 19 (Covid-19) causes disturbances in the bio-psycho-socio-spiritual conditions of Covid-19 patients undergoing isolation. Family health and resilience is important in this problem. The purpose of this study was to analyze the relationship between family health and the bio-psycho-socio-spiritual conditions of Covid-19 patients at Aparma Unipdu Jombang. The design of this research is correlational descriptive with a cross sectional approach. The population of this study were 40 patients. The sampling technique used was total sampling. The instrument in this study used a bio-psycho-socio and spiritual questionnaire and a family health questionnaire using the APGAR family score questionnaire. Data analysis used the spearman correlation test with = 0.05. The results showed that the biological condition of the patient was 45% high, the psychological condition was 47.5% high, the sociological condition was 45% high, in the spiritual condition 45% showed a high score. The results of the statistical test showed a p-value value of 0.00 <0.05, which means that there is a relationship between family health and the biopsychosociospiritual condition of Covid-19 patients at Aparma Unipdu Jombang. So it can be concluded that the health of the family is very influential on the bio-psycho-socio-spiritual conditions during the isolation period. Family resilience, the running of family functions and a strong family structure are needed by the family to always maintain family health and provide support to family members undergoing isolation.Keywords: bio-psycho-socio-spiritual, covid-19, isolation, family health